Y=8
A horizonal line means y equals something. When you have a given point on the horizontal line you know the answer, which is the value of y in the given point.
Answer:
A) 6.0
Step-by-step explanation:
First, total amount of hours, since average is sum of the numbers by how many numbers there is.
Day 1=8x2 hr
Day 2=6x1 hr
Day 3=4x2 hr
which is, 16+6+8=30
then divide 30 by how many days there is, which is 5 days.
30/5=6
Answer:
The distance between Harry’s home and his office? is 15 miles.
Step-by-step explanation:
The speed, distance time formula is:
![Speed(s)=\frac{Distance(d)}{Time(t)}](https://tex.z-dn.net/?f=Speed%28s%29%3D%5Cfrac%7BDistance%28d%29%7D%7BTime%28t%29%7D)
Given:
Speed (<em>s</em>) = 30 miles/hour
Then the relation between distance and time is:
![s=\frac{d}{t} \\30=\frac{d}{t}\\d=30t...(i)](https://tex.z-dn.net/?f=s%3D%5Cfrac%7Bd%7D%7Bt%7D%20%5C%5C30%3D%5Cfrac%7Bd%7D%7Bt%7D%5C%5Cd%3D30t...%28i%29)
If Speed was 60 miles/hour the time taken is
hours.
Then the relation between distance and time is:
![s=\frac{d}{t} \\60=\frac{d}{(t-\frac{1}{4}) }\\d=60t-15...(ii)](https://tex.z-dn.net/?f=s%3D%5Cfrac%7Bd%7D%7Bt%7D%20%5C%5C60%3D%5Cfrac%7Bd%7D%7B%28t-%5Cfrac%7B1%7D%7B4%7D%29%20%7D%5C%5Cd%3D60t-15...%28ii%29)
Use the value of <em>d</em> = 30t in (ii)
<em />
<em />
Determine the distance as follows:
![d=30t\\=30\times\frac{1}{2} \\=15\ miles](https://tex.z-dn.net/?f=d%3D30t%5C%5C%3D30%5Ctimes%5Cfrac%7B1%7D%7B2%7D%20%5C%5C%3D15%5C%20miles)
Thus, the distance between Harry’s home and his office? is 15 miles.
Answer: $4.50
Step-by-step explanation: If it is 50% off then you take the price of $2.25 and double it. So 2 times $2.25 which is $4.50.
The first thing we are going to do to solve the problem is to define what associative property is:
Associative property Property that is fulfilled if, given any three elements of a given set, it is verified that there is an operation that verifies equality
An expression that meets the definition is:
(x + 3) + 7 = x + (3 + 7)
We observe that both members of equality are identical, but written in different ways.
Answer:
B) (x + 3) + 7 = x + (3 + 7)